Development of constructivism-based physics tools to build generic science skills for high school students - Ardiansyah Ardianyah (Jurnal Pijar Mipa, 2023)
This research and development aim to develop constructivism-based physics teaching aids to build students' generic science skills on static fluid material. The research subjects chosen were class XI Senior High School 2 Kilo, semester I, studying static fluid material for the 2022/2023 academic year. The validation results for the development of constructivism-based physics teaching aids to build Generic Science Skills for high school students on static fluid material show an average score of 0.75 with a percentage of 22.43% for very good criteria, an average score of 2.75 with a percentage of 78.57% for good criteria. At the same time, the categories are sufficient, lacking, and very unfavorable, each with an average score of 0 with a percentage of 0.00%. It indicates that the validator assesses the aspect of the teaching aids as good. The development of constructivism-based physics teaching aids on static fluid material can build students' Generic Science Skills, shown in the N-Gain percentage of 70.65% with the high category. Students also responded positively to the development of constructivism-based teaching aids in building Generic Science Skills. It was indicated by the average student responding strongly agree 37.60% and giving a response of agree 44.00% while responding disagree 9.80%, strongly disagree 8.60%.